Teknik Imobilisasi Sederhana pada Penanganan Cedera di Fasilitas Kesehatan Tingkat Pertama: (Studi Observasi di Puskesmas Laja) - Silvester Albertus Dhogo; Maria Natalia Kua; Robertus Lili Bile (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2026)
Injury cases in primary health centers are quite common and require proper initial treatment to prevent complications. Simple immobilization is one important method for early injury management, aiming to restrict movement in the injured area to reduce pain, prevent swelling from worsening, and avoid further tissue damage. This study was conducted to observe how simple immobilization techniques are actually applied in injury management at community health centers, specifically at Puskesmas Laja. The method used descriptive observational study, where we directly observed the patient care process and conducted brief interviews with health workers. The observation results showed that simple immobilization techniques such as using splints, elastic bandages, and temporary movement restriction were applied according to the injury condition and available resources. These techniques were quite effective as initial steps before patient referral if needed. In conclusion, simple immobilization techniques play an important role in injury management at community health centers and need continuous development through training and adequate equipment availability.